Renaissance Texts, Medieval Subjectivities : Rethinking Petrarchan Desire from Wyatt to Shakespeare - Sokolov, D. A. (Danila Alekseevich) (Book collections on Project MUSE., 2017)
In a major contribution to the burgeoning area of study that crosses between early modern texts and premodern cultures, Danila Sokolov argues for the necessity of reading the work of English Petrarchan writers in light of earlier medieval forms of poetic subjectivity. By doing just that, this book directly challenges one of the most enduring myths of contemporary criticism and shows that the many innovations associated with the poetry of Petrarchism derive from medieval subjectivities that continue to inform modern ideas of selfhood and modernity more generally.